Distribution characteristics of the summer precipitation raindrop spectrum on the Qinghai–Tibet Plateau - F. Wang; F. Wang; Y. Duan; Y. Huo; Y. Huo; Y. Cao; Q. Wang; T. Zhang; J. Liu; G. Cao (Atmospheric Measurement Techniques)
To enhance the precision of precipitation forecasting in the Qinghai–Tibet Plateau region, a comprehensive study of both macro- and micro-characteristics of local precipitation is imperative. In this study, we investigated the particle size distribution, droplet velocity, droplet number density, Z–I (radar reflectivity–rainfall intensity) relationship, and gamma distribution of precipitation droplet spectra with a single precipitation duration of at least 20 min and precipitation of 5 mm or more at four stations (Nyalam, Lhasa, Shigatse, and Naqu) in Tibet during recent years from June to August. The results are as follows: (1) in the fitting relationship curve between precipitation raindrop spectral particle size and falling speed at the four stations in Tibet, when the particle size was less than 1.5 mm, the four lines essentially coincided. When the particle size exceeded 1.5 mm, the speed in Nyalam was the highest, followed by Naqu, and the speed in Lhasa was the lowest. The falling speed of particles correlated with altitude. (2) The five microphysical characteristics (mean diameter (Dm), average volume diameter (Dv), mode diameter (Dd), dominant diameter (Dp), and median diameter (Dnd)) at the four stations have different correlation relationships with altitude under different rainfall intensities. Dm exhibits a negative correlation with altitude at the same rainfall intensity; in contrast, Dv shows a positive correlation with altitude. For microphysical parameters such as Dd and Dp, a rainfall intensity of 10 mm h−1 serves as the boundary line, and they have different correlation relationships with altitude under the same rainfall intensity level. (3) The Z–I relationships at the four stations exhibited variations. Owing to the proximity in altitude between Lhasa and Shigatse, as well as between Nyalam and Nagqu, the coefficient a and index b in the Z–I relationships of the two groups of sites were relatively similar. (4) The fitting curves of the exponential and gamma distributions of the precipitation particle size at the aforementioned four stations are largely comparable. The exponential distribution fitting exhibits a slightly better effect. The parameter μ in the gamma distribution decreases with an increase in altitude, while N0 and λ in the exponential distribution show a clear upward trend with altitude.